2021
DOI: 10.1177/2158244020982605
|View full text |Cite
|
Sign up to set email alerts
|

Participatory: Stakeholder’s Engagement Toward Dengue Control Techniques in Klang Valley, Malaysia

Abstract: Dengue is the main health problem in Malaysia. One of the main causes of dengue is the lack of participation in combating dengue. To improve participation, stakeholder’s engagement is considered the best solution which promotes an effective way of forming good governance. Engagement involves a level of knowledge, awareness, and understanding through past intended behavior. The objective of this study is to assess and compare the level of engagement of stakeholders toward dengue control techniques. A survey was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Multisectoral partnerships such as participatory research have been shown to be effective in raising awareness and rallying local communities in dengue control efforts [45,46]. By engaging relevant stakeholders such as community members, healthcare professionals, and government agencies through PR, dengue control strategies can be more effective [47,48]. All these partnerships can foster close collaboration and knowledge sharing that lead to a more comprehensive and community-centered approach to combating dengue [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Multisectoral partnerships such as participatory research have been shown to be effective in raising awareness and rallying local communities in dengue control efforts [45,46]. By engaging relevant stakeholders such as community members, healthcare professionals, and government agencies through PR, dengue control strategies can be more effective [47,48]. All these partnerships can foster close collaboration and knowledge sharing that lead to a more comprehensive and community-centered approach to combating dengue [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant efforts made by the government, including mosquito breeding eradication, 3M Plus, one-house one-larvae observer program, and more, these achievements hold little significance without the active participation of the community [29] necessary not only during DHF outbreaks when the community reacts but also under normal circumstances when no efforts are made to control DHF [30]. Communities should strive to meet health needs and collaborate to solve health problems [31]- [33]. The community needs to be equipped with knowledge about the program so that they can play an active role and determine the success of the program [33].…”
Section: Outcomementioning
confidence: 99%
“…25,26 Long-term sustainable interventional strategy necessitates active community involvement and stakeholder engagement. 27,28 Previous studies have suggested that core elements of the interventions encompass discussion with relevant stakeholders to set up a local steering committee comprised of epidemiologists, entomologists, ecologists, social scientists, and educational professionals, formation of working groups at grassroots level to promote community participation in environmental management, establishment of effective collaborations between community working groups, health services, and the government sectors, as well as integration of the interventional programme into national or regional vector control action plan. 27 Specific public health measures include performing large-scale dengue surveillance testing in tandem with community-based environmental management (e.g.…”
mentioning
confidence: 99%